Rehabilitation in the case of Primary and Secondary CNS and PNS Tumors in the practice of family doctor : study guide for the practical classes and individual work for 6th-years students of international faculty - Mykhailovska, N. S.; Grytsay, A. V.; Михайловська, Наталія Сергіївна; Грицай, Ганна Володимирівна (Запорізький державний медико-фармацевтичний університет, 2023)
Study guide compiled in accordance with the program of «General practice - family medicine». Guidelines are intended to help students prepare for practical classes and learn the material. Can be used for training of 6th-years students of international faculty, discipline «General practice - family medicine».